Une appellation transnationale pour l’Océan Pacifique: Te moana nui a Kiwa (Nouvelle-Zélande) - Te moana nui a Hiva (Tahiti) - Bruno Saura (Archivio Antropologico Mediterraneo, 2022)
For a generation, the name « (Te) moana nui a Hiva» has been used more and more widely, in Tahiti, to designate, in an extensive way, the Pacific Ocean. It seems to be a contemporary Tahitian adaptation of an older Maori - New Zealand - name, «(Te) moana nui a Kiwa». After an exploration of Polynesian traditions, an analysis of the term moana (ocean) and the mā’ohi (native Tahitian) nomenclature related to the sea, the ocean, will be made. Then, we will proceed to a return to the term Hiva, recurrent in the toponymy and in the ancient culture of the islands of Eastern Polynesia, bearing multiple meanings. The ultimate question that will be asked is related to the existence - or not - of a broad, extensive vision of the ocean, by the ancient Polynesians of this cultural area.